The strongest link: Legitimacy of top management diversity, sex stereotypes and the rise of women in human resource management 1995 - 2004 - Astrid Reichel; Julia Brandl; Wolfgang Mayrhofer (Management Revue, 2010)
Over the last decades, HRM scholars associated the inclusion of women into HRM with the occupation's loss of status. Such views have difficulties to explain more recent developments in Europe that show a co-evolution of feminization and status increase of HRM. In this article, we review these developments and offer an explanation that accounts for them. Linking neo-institutional arguments with literature on sex stereotypes, we suggest that allocating women to HRM offers a solution for organizations to deal with growing demands for enhancing diversity within top management without giving up the traditional division of female and male work. We show how the patterns of the inclusion of women into HRM in 11 European countries between 1995 and 2004 support this explanation.
Keywords: 650; HRM; occupational status; occupational feminization; sex stereotypes; institutional pressures